MEDIA SOSIAL DAN INTERNET DALAM KETELIBATAN INFORMASI POLITIK DAN PEMILIHAN UMUM - Adinugroho, Billy; Prisanto, Guntur Freddy; Irwansyah, Irwansyah; Ernungtyas, Niken Febrina (Universitas 17 Agustus 1945 Surabaya, 2019)
Social media and Internet websites have a role in election campaigns as a political information source. The new media also allows each individual to express political attitudes and support openness. This indicates that new media, especially social media, is influencing the search for political information and beliefs to participate in elections. This article aims to describe the influence of attention to social media, attention to traditional Internet sources and online expressions on the political self-efficacy and situational political involvement. The research method uses a quantitative approach by conducting an online survey of 100 respondents purposively. Data analysis uses univariate analysis for demographic data. The hypotheses are tested by using a simple linear regression test. There are six hypotheses tested in this study and all hypotheses are supported statistically. This study shows that attention to social media has a stronger influence on political self-efficacy and situational political involvement than tradistional Internet sources and online expressions.Keywords: social media, Internet, politics, political self-efficacy, situational political involvement